PERAN IKLAN DALAM MENINGKATKAN MINAT MENABUNG MASYARAKAT PADA PT BANK SYARIAH MANDIRI CABANG KOTA LANGSA - febi febi; Abdul Hamid; Mutia Sumarni; Riski Purwaliani (Fakultas Ekonomi dan Bisnis Islam IAIN Langsa, 2019)
Advertising always plays an important role in increasing the interest of saving the community, so advertising needs to be done to inform, persuade and attract people, and have added value for the community. With advertising, the public can recognize Banking products contained in Bank Syariah Mandiri Branch of Langsa City and the community can distinguish which products suited to their needs and eliminate the public concern about usury practices that occur especially for the people of Langsa city. Based on the discussion of this thesis the author took some problems that is, how advertising is done by Bank Syariah Mandiri Branch Langsa City and how the role of advertising in increasing interest to save the community. The research method used in this thesis is a qualitative descriptive method with interviews and documentation as a method of data collection to se the role of advertising in increasing interest in saving the community at Bank Syariah Mandiri Branch Langsa City. From the results of this study it is known that the ad performed Bank Syariah Mandiri has a role in increasing interest in saving society, with the media used are banners and brochures. Advertising is done as a supporter of direct socialization to prospective customers conducted by Bank Syariah Mandiri Branch Langsa City. From the results of research conducted by the author with the public that the Bank Syariah Mandiri Branch Langsa has a complete brochure and the products offered are also diverse and different from other banks so that the most important role of advertising is the brochure. Brochures can strengthen the interest of customers to continue to save in Bank Syariah Mandiri and use other products offered. However, some of them said that the Bank Syariah Mandiri Langsa branches do not do advertising, some of them have a book of savings Bank Syariah Mandiri because of other interests